Antioxidant activities and free amino acid content of rice responded to xanthomonas oryzae pv oryzae infection under phosphate starvation condition - Mai Huong, To Thi; Phuong Nga, Mai Thi (Vietnam Journal of Biotechnology, 2023)
Rice productivity strongly affects food security worldwide, especially in Asia, where rice is served as a staple food. However, rice productivity was threatened by numbers of environmental stresses, including Xanthomonas oryzae pv oryzae (Xoo) disease. Xoo is causing significant losses to rice production around the world. Furthermore, thanks to the significant function of phosphate (Pi) in nucleic acid and cell membrane structure, energy-transporting molecules, photosynthesis and respiration, a sufficient supply of Pi for rice plants is essential. Our previous studies had demonstrated the effect of low Pi in increasing Xoo tolerance in rice. In the present study, two-biochemical processes responsible for this tolerance were investigated by analyzing antioxidant enzyme activities and free amino acid profile produced by Xoo infected rice plants under Pi starvation and full Pi conditions. Two selected rice cultivars, G22 and G299, were used as plant materials. After two weeks of 6-week-old plants infected with Xoo, peroxidase and catalase activities in the plants under the low Pi condition were significant increased. Amino acids belonging to the glutamic, serine and pyruvate families, especially serine and proline accumulated the higher levels in plants under low Pi conditions compared to full Pi. In our two studied rice cultivars, the improvement in both antioxidant enzymes and free amino acid was found cultivar-dependence, the sensitive to low Pi G299 cultivar responsed stronger than the tolerant to low Pi G22 cultivar. The results from this study provide more detail about the possible mechanism how rice plants tolerant to Xoo under the Pi starvation condition and can suggest a strategy for green agriculture in dealing with Xoo infection by considering the interaction between Pi starvation and the Xoo response.